Pattern of Injuries among Two or Four Wheeler Occupants in Fatal Road Traffic Injuries - S, Yadukul; Devadass, PK; Gururaj, G (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: Every day, we read, listen, or witness, injuries in our day to day lives. Over time, it has moved from 5th to 3rd to 1st page of our newspapers. Some days, it is not uncommon to see the entire page of our newspaper filled with news about injury and violence. On television channels, even on prime time, injury and violence has occupied the center stage. Many times, the ‘breaking news’ is only deaths due to road crashes, suicides, mass burns and blood loaded violence. The present study is aimed at analyzing the various types of injuries that occur in road traffic injuries and to take necessary actions by the concerned authority to prevent such incidents in the future. Methods: In this study, we studied the various patterns of injuries sustained by the occupants of two/four wheeler during fatal road traffic injuries. A total number of 238 cases (those who died in road traffic injuries) were included in the study for a period of 2 years from October 2010 to September 2012 in Department of Forensic Medicine and Toxicology, Bangalore Medical College and Research Institute, Bengaluru. Results: Among the cases studied in our study (n=238), majority of the victims were males constituting 94% of the cases and in age-wise distribution of cases, age group of 21-30 years (46.2%) followed by 31-40 years (21.4%) constitutes to about 2/3rd of the cases. Time of injury among the cases studied showed that highest incidence being during the night times (18:01-00:00) which constitutes 44.11%. Among the road user category, two wheeler riders (78.15%) formed the major contributors for road traffic injury. Conclusion: In the present study, it is very clear that the middle aged, male bike riders are more prone for fatal road traffic injuries. Hence, Government should take proper initiatives in the future to focus on these high risk individuals to prevent such fatalities.